An empirical research on the financial distress risk in the garden and construction industry - GUAN, Jianlin (Institutional Knowledge at Singapore Management University, 2023)
In recent years, the garden and construction industry has faced significant financial distressdue to the downward pressure on the macro economy. This financial distress not onlyposesrisks to the financial stability and management of enterprises but also has far-reachingimpactson society. This paper utilizes various analytical methods such as case analysis, empirical analysis, andevent analysis to derive the following conclusions:(1)The participation of garden constructionindustry enterprises in public-private partnership (PPP) projects leads to increased financial distress.(2)The higher the debt ratio of the local government where listed gardenandconstruction enterprises are located, the greater the financial distress theyexperience.(3)Enterprises in the garden and construction industry, whose primary businessinvolves the real estate industry, may be able to alleviate their financial distress in theearlystages. However, they struggle to reduce their financial distress during periods of weaknessinthe real estate industry, particularly after 2019.(4)The financial distress of listed gardenandconstruction enterprises is influenced by the aggressiveness of their business strategies. Amoreaggressive strategy corresponds to higher levels of financial distress.(5)The financial distressof garden and construction enterprises is inversely related to the shareholding ratio of the largest shareholders. Higher shareholding ratios are associated with lower levels of financial distress.(6)The issuance of green bonds by listed garden and construction enterprises generatespositive excess yield and significantly improves their stock prices. This is primarily due tothefact that green bonds can reduce the debt financing costs of these companies andaddressinvestment and financing maturity mismatches. Based on these findings, the following policy suggestions are proposed:(1)Listedenterprises in the garden and construction industry should carefully evaluate their financial capacity before participating in PPP projects. Excessive reliance on such projects canworsenthe investment and financing term structure of these enterprises.(2)It is advisable for listedenterprises in the garden and construction industry to collaborate with local governments that have a relatively low debt ratio and strong financial strength. This can help mitigatethespillover effect of local government debt risks.(3)The garden and construction enterprises arewell-suited to an equity structure with a relatively high shareholding ratio of the largest shareholders. These enterprises should adopt a steady development strategy toreduceaggressive investments and high-leverage financing.(4)Encouraging listed gardenandconstruction enterprises to issue green bonds and engage in businesses related to environmental protection and people's livelihoods can help reduce their financing costs and address investment and financing term structure challenges.